Contents of school textbooks as a factor of ecological education of junior pupils in Zakarpattia (1919-1939) - Liubomyra Iliichuk (Vasyl Stefanyk Precarpathian National University, 2017)
Polish experience of decentralization of management in the sphere of education has been studied in the article. In particular, the essence of the terms decentralization and decentralization of education has been revealed. Modern state and legal framework of the process of education decentralization in Ukraine have been analyzed. Key words: decentralization, sphere of education, Republic of Poland, reforms.